ENTREPRENEURIAL KNOWLEDGE, ENTREPRENEURIAL INTENTION, DAN ENTREPRENEURIAL ORIENTATION PADA PENDIDIKAN ILMU AKUNTANSI - Tanjaya, Clarisia; Radianto, Wirawan ED (Media Akuntansi dan Perpajakan Indonesia, 2020)
This study aims to prove whether there are differences in entrepreneurial knowledge, entrepreneurial intention, and entrepreneurial orientation in accounting students in higher education. The problem with this research is whether there are differences in entrepreneurial knowledge, entrepreneurial intention, and entrepreneurial orientation between junior students and senior students. This research used quantitative analysis and survey method is applied to gather information. Then analyze the data using the independent sample T test. The results of this study are there are differences in entrepreneurial knowledge, entrepreneurial intention, and entrepreneurial orientation between junior and senior accounting students.